(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The lexico-semantic field of «war» in the works by O. Gonchar is analyzed in the article. Special attention is paid to the linguistic expression of a tragedy of war.